Single nucleotide polymorphisms in a regulatory site of VRN-A1 first intron are associated with differences in vernalization requirement in winter wheat - Kippes, Nestor (Mol Genet Genomics, 2018)
Winter wheats require a long exposure to cold temperatures (vernalization) to accelerate flowering. However, varieties differ in the length of the period of cold required to saturate the vernalization response. Here we show that single nucleotide polymorphisms (SNP) at the binding site of the GRP2 protein in the VRN-A1 first intron (henceforth, RIP3) are associated with significant differences in heading time after a partial vernalization treatment. The ancestral winter VRN-A1 allele in ‘Triple Dirk C’ has one SNP in the RIP3 region (1_SNP) relative to the canonical RIP3 sequence, whereas the derived ‘Jagger’ allele has three SNPs (3_SNPs). Both varieties have a single VRN-A1 copy encoding identical proteins. In an F(2) population generated from a cross between these two varieties, plants with the 3_SNPs haplotype headed significantly earlier (P < 0.001) than those with the 1_SNP haplotype, both in the absence of vernalization (17 days difference) and after 3-weeks of vernalization (11 days difference). Plants with the 3_SNPs haplotype showed higher VRN-A1 transcript levels than those with the 1_SNP haplotype. The 3_SNPs haplotype was also associated with early heading in a panel of 127 winter wheat varieties grown in three separate controlled-environment experiments under partial vernalization (36 to 54 days, P < 0.001) and one experiment under field conditions (21 d, P < 0.0001). The RIP3 polymorphisms can be used by wheat breeders to develop winter wheat varieties adapted to regions with different duration or intensity of the cold season. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00438-018-1455-0) contains supplementary material, which is available to authorized users.